Easter Sunday - Chandrasekhar, Jay; Koy, Jo; Gaston, Lydia; Wardell, Brandon (Universal, 2022)
Follows Joe as he returns home to his Filipino-American family for Easter Sunday.
A man returns home to celebrate Easter with his riotous, bickering, eating, drinking, laughing, loving family.
Wide screen 2.35:1.
Jo Koy, Lydia Gaston, Brandon Wardell, Eva Noblezada, Carly Pope, Jay Chandrasekhar, Tia Carrere.
MPAA rating: PG-13.
DVD.
Keywords: Filipino American families -- Drama; Easter -- Drama; Comedy films; Feature films; Fiction films